Potensi ekstrak etanol 70% akar saluang balum (Lavanga sarmentosa blume kurz) terhadap kualitas dan viabilitas sperma mencit - Syarif, Yaumi Musfirah; Bachri, Moch Saiful; Nurani, Laela Hayu (Pharmaciana, 2016)
The present study tried to investigate potency of L. sarmentosa root extract on quality and viability of mice sperm.This study used 25 Swiss male mice were randomly divided into five experimental groups of 5. The ethanolic extract of L. Sarmentosa (100, 200, 400 mg/kg b.w/days), control and X-gra were administered orally for 14 days. The animals were evaluated for sperma quality (sperm count and sperm motility) and viability at 14 days treatment. The results showed that administration of L.sarmentosa roots extract significantly increasing the sperm count (970x106cell/mL) at 400 mg/kg b.w/days (P 0.0040). The extract dose of 200 mg/Kg b.w and 400 mg/Kg b.w had the highest motility values (95%). Viability of sperm are 83.8%; 96.0%; 87.8% respectively at a dose of 100 mg/kg b.w, 200 mg/kg b.w and 400 mg/kg b.w. Present finding oral administration ofÂ L. sarmentosa roots extract has a potency of the quality and viability of mice sperm.